2023
DOI: 10.1029/2022gl101185
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of the 15 January 2022 Tonga Event: Development of Super Equatorial Plasma Bubbles

Abstract: We present high‐resolution simulation results of the response of the ionosphere/plasmasphere system to the 15 January 2022 Tonga volcanic eruption. We use the coupled Sami3 is Also a Model of the Ionosphere ionosphere/plasmasphere model and the HIgh Altitude Mechanistic general Circulation Model whole atmosphere model with primary atmospheric gravity wave effects from the Model for gravity wavE SOurces, Ray trAcing and reConstruction model. We find that the Tonga eruption produced a “super” equatorial plasma b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
(48 reference statements)
4
24
1
Order By: Relevance
“…While the 30°‐wide EPB in Huba et al. (2022)'s simulation was not clearly observed in the present study (possibly due to its limited latitudinal extent), the observation of a longitudinally narrow, high‐altitude and low‐density structure over northeastern Australia is consistent with the very‐high‐altitude EPBs in Huba et al. (2022)'s study; noting the rather reasonable differences in observed versus modeled location.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…While the 30°‐wide EPB in Huba et al. (2022)'s simulation was not clearly observed in the present study (possibly due to its limited latitudinal extent), the observation of a longitudinally narrow, high‐altitude and low‐density structure over northeastern Australia is consistent with the very‐high‐altitude EPBs in Huba et al. (2022)'s study; noting the rather reasonable differences in observed versus modeled location.…”
Section: Discussionsupporting
confidence: 70%
“…(2022)'s simulation was not clearly observed in the present study (possibly due to its limited latitudinal extent), the observation of a longitudinally narrow, high‐altitude and low‐density structure over northeastern Australia is consistent with the very‐high‐altitude EPBs in Huba et al. (2022)'s study; noting the rather reasonable differences in observed versus modeled location. This structure over northeastern Australia thus fits the definition of a “super bubble” according to Ma and Maruyama (2006) and is in good agreement with the results of Rajesh et al.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A companion paper inputted the HIAMCM neutral wind into SAMI3. They found that the Tonga event created a “super” equatorial plasma bubble that extended ∼30° in longitude and up to 500 km in altitude, and had a density depletion of three orders of magnitude (Huba et al., 2023).…”
Section: Discussionmentioning
confidence: 99%